Observation of heterospecific mating attempt of Blue Chaser Libellula fulva Müller, 1764 and Broad-bodied Chaser L. depressa Linnaeus, 1758 (Anisoptera: Libellulidae) - Matjaž Bedjanič (Natura Sloveniae)
A successful copula formation between a male of Libellula fulva and a female of L. depressa was documented photographically on 23. 6. 2022 at a small stream in the Natura 2000 site Ličenca pri Poljčanah in NE Slovenia. This represents the first record of an anomalous mating attempt with copula formation between the species involved. Their distribution in Slovenia as well as syntopic and syntemporal observations in the country are presented and briefly discussed, as are the site-specific factors and aged female coloration that may have contributed to the described rare attempt of heterospecific mating.